YOUTUBE DAN KEBHINNEKAAN (PERSEPSI AKADEMISI TERHADAP YOUTUBE SEBAGAI MEDIA ALTERNATIF PENYAMPAI PESAN KEBHINNEKAAN) - Haryo Kusumo Aji (RESEARCH FAIR UNISRI, 2018)
This research is motivated by the rise of negative news concerning the issue of SARA,radicalism and so on that spread in cyberspace. Social media becomes the easiest place to spreadcontent like this because of the easy access given to share any posts. Youtube as the largest videobasedsocial media became one of the reference individuals to find information based on audio andvisual. An academic with his academic background has a certain perception of this youtube mediain conveying the message of diversity.By using qualitative approach interpretive and case study method, hence got result ofresearch conducted by academics at Slamet Riyadi University. From the attention variablesobtained that someone's motive in watching youtube impressions is to know the clarity of anexisting information, because of this media based on audio visual. While the external factor of thisvariable is the ease of using youtube to share in multi platform. For Interpretation variablesobtained that the value of the individual is in terms of usefulness using this medium is to increaseknowledge, also in the satisfaction as a place of entertainment. In the experience variables fromindividuals in the world of academics are for improving interest for pay attention to topics relatedto education. Then, in the culture variables, namely religion and belief become the basis inperceiving a show that contains SARA issues. Individuals want to see how religion deals withemerging issues. Then, in the expectations variables shows how individual expectations to furthermultiply positive content in social media in order to muffle the negative content so that thediversity of the Indonesian nation more realized.Kata kunci: Youtube, Kebhinnekaan, persepsi, akademisi, media alternatif